Extended pancreatectomy: does it have a role in the contemporary management of pancreatic adenocarcinoma? - Kaiser, Jörg; Hackert, Thilo; Büchler, Markus W. (Digestive surgery, 2017)
Background: Pancreatic cancer is a low-incident but highly mortal disease. Surgery is still the preferred treatment option for resectable pancreatic cancer as it offers the only realistic chance for cure. As many patients present with locally advanced disease, which is generally considered as not amenable to surgical treatment, it is important to know the limits of surgical therapy in this disease. Methods: In this review, the indication and outcomes of extended pancreatectomies as well as the alternative treatment options for locally advanced pancreatic cancer are described. Furthermore, controversies as well as ongoing and future directions for the treatment options of locally advanced pancreatic cancer are discussed. Results: Extended pancreatectomy can be performed with higher morbidity and mortality rates in patients with locally advanced pancreatic cancer compared to patients undergoing formal pancreatic resections. These procedures offer significant advantages with respect to both perioperative results and to long-term outcome when compared to chemotherapy. Conclusion: Due to the higher morbidity and mortality rates, these operations should be limited to specialist units with great experience in pancreatic surgery as well as experience in peri- and post-operative management of patients with pancreatic diseases.